Sexual risky behaviors in violence survivors aged 14 to 18 who sought care at a tertiary-level hospital in Mexico - Eugenia Pérez-García; Ángel Eduardo Velasco-Rojano; Alejandra García-Saisó; Aarón Rodríguez-Caballero; Jorge Luis Montes-Domínguez; Yiblia Krystal Salgado-Cedano; Lydia Estela Zerón Gutiérrez (Child Protection and Practice)
Background: Sexual violence can lead to risky sexual behaviors that increase the likelihood of adverse outcomes. Collecting information on these behaviors is crucial to support survivors before adulthood. Objective: This study aimed to assess the need for attention to risky sexual behaviors among adolescents at a specialized violence care clinic in Mexico City. Participants and setting: 173 medical records from adolescents aged 14 to 18 (average age: 15.15 years) who sought care at a tertiary-level hospital were analyzed, with 52.02% females and 47.98% males. Methods: A cross-sectional study reviewed records from 2018 to 2023. Three judges independently coded information on risky sexual behaviors, including unprotected sex, sexualized substance use, and relationships with older partners. Results: All participants reported at least one risky sexual behavior, with unprotected sex being the most common (68.78% of records). The least reported was sex with casual partners, noted in only two records. Conclusion: The high prevalence (88%) of risky sexual behaviors among violence survivors highlights the necessity for targeted prevention and intervention programs, as these behaviors are associated with adverse outcomes.